Isolation of an antimicrobial‐resistant, biofilm‐forming, Klebsiella grimontii isolate from a reusable water bottle. Issue 6 (3rd March 2020) - Hubbard, Alasdair T. M.; Newire, Enas; Botelho, João; Reiné, Jesús; Wright, Elli; Murphy, Emma A; Hutton, William; Roberts, Adam P.
Abstract: A reusable water bottle was swabbed as part of the citizen science project "Swab and Send, " and a Klebsiella grimontii isolate was recovered on chromogenic agar and designated SS141. Whole‐genome sequencing of SS141 showed it has the potential to be a human pathogen as it contains the biosynthetic gene cluster for the potent cytotoxin, kleboxymycin, and genes for other virulence factors. The genome also contains the antibiotic‐resistant genes, bla OXY‐6‐4, and a variant of fosA, which is likely to explain the observed resistance to ampicillin, amoxicillin, and fosfomycin. We have also shown that SS141 forms biofilms on both polystyrene and polypropylene surfaces, providing a reasonable explanation for its ability to colonize a reusable water bottle. With the increasing use of reusable water bottles as an alternative to disposables and a strong forecast for growth in this industry over the next decade, this study highlights the need for cleanliness comparable to other reusable culinary items. Abstract : A reusable water bottle was swabbed as part of the citizen science project "Swab and Send, " and a Klebsiella grimontii isolate was recovered on chromogenic agar and designated SS141. Whole‐genome sequencing of SS141 showed it has the potential to be a human pathogen as it contains the biosynthetic gene cluster for the potent cytotoxin, kleboxymycin, and genes for other virulence factors and antibiotic resistance. We have also shown that SS141 is a potent biofilm former, providing a reasonable explanation for its ability to colonize a reusable water bottle.